ANTI-INFLAMMATORY ACTIVITY OF METHANOLIC EXTRACT OF ROOTS OF GLYCOSMIS PENTAPHYLLA - Arora, Namita; Arora, Pankaj (Asian Journal of Pharmaceutical Research and Development, 2016)
The plant Glycosmis pentaphylla corr. belongs to the family Rutaceae. This plant has great medicinal value and is widely distributed in India. The anti-inflammatory effect of methanolic extract of roots of G. pentaphylla was studied using carrageenan and egg albumin-induced rat paw edema, xylene induced mouse ear edema and formaldehyde induced arthritis inflammation tests at doses of 50-400 mg/kg, intra peritoneally. The extract produced a significant (P<0.05) dose dependant inhibition of edema formation in all four methods. The results of pharmacological tests performed in the present study suggest that the methanolic extract of G. pentaphylla possess anti-inflammatory effect and these findings seem to justify the use of plant in traditional Indian medicine in the treatment of inflammation.